What is multimodal critical discourse studies? - Junqueira, Thaís Lôbo (Discurso em Cena, 2017)
MACHIN, D. What is multimodal critical discourse studies? Critical Discourse Studies. Reino Unido: Routledge Taylor & Francis Group, v. 10, n. 4, p. 347-355, 2013.